Asymmetric synthesis of alpha-alkylated aldehydes using terminal epoxide-derived chiral enamines. - Hodgson, D; Kaka, N (John Wiley and Sons, 2008)
(Chemical Equation Presented) Effective discrimination: Efficient lithium amide-induced terminal epoxide-enamine transformation provides the first enamines capable of generating α-alkylated aldehydes with high asymmetric induction by intermolecular nucleophilic substitution (see scheme). © 2008 Wiley-VCH Verlag GmbH and Co. KGaA.